Development of a skeleton-specific antibody and Au nanoparticle-based immunochromatographic sensor for simultaneous detection of various tadalafil adulterants in health food. Issue 1 (1st January 2019) - He, Fan; Zou, Tingting; Yang, Jinyi; Wang, Hong; Deng, Lihua; Tian, Yuanxin; Xu, Zhenlin; Sun, Yuanming; Lei, Hongtao; Tan, Xuecai; Shen, Yudong
ABSTRACT: In this work, a rapid, convenient and sensitive Au nanoparticle-based immunochromatographic sensor (AuNPs-ICS) for simultaneous detection of various tadalafil adulterants in health food was established for the first time, based on one high affinity and broad-spectrum antibody through skeleton-specific hapten design according to the common structure of tadalafil drugs. This immunochromatographic sensor was developed by the polyclonal antibody conjugated with AuNPs and the IC50 was 10.04 ng mL −1 for tadalafil and 9.55, 11.46, 17.01 ng mL −1 for amino tadalafil, acetamino tadalafil and nortadalafil, respectively. The limit of detection results could be obtained visually by naked eyes for and computationally by the hand-held immunochromatography reader. The sensor could specially detect Tadalafil and its analogs within 10 min in health food samples, and the close correlation with UPLC-MS/MS method showed the sensor was accurate and reliable, which could apply to on site detection Tadalafil and its analogs rapidly and accurately.